Recent advances in SARS-CoV-2 Spike protein and RBD mutations comparison between new variants Alpha (B.1.1.7, United Kingdom), Beta (B.1.351, South Africa), Gamma (P.1, Brazil) and Delta (B.1.617.2, India) - Paulo R.S. Sanches; Ives Charlie-Silva; Helyson L.B. Braz; Cíntia Bittar; Marilia Freitas Calmon; Paula Rahal; Eduardo M. Cilli (Elsevier, 2021)
New variants of SARS-CoV-2 Alpha (B.1.1.7); Beta (B.1.351) Gamma (P.1) and Delta (B.1.617.2) quickly spread in the UK, South Africa, Brazil and India, respectively. To address whether mutations in SARS-CoV-2 RBD spike protein could affect virus infectivity, peptides containing RBD amino acids mutations have been constructed and interacted with human ACE2 by computational methods. Our results suggest that mutations in RBD amino acids K417, E484, L452, T478 and N501 are expressively increasing the affinity of this protein with human angiotensin-converting enzyme 2 (ACE2), consequently, variants Alpha (B.1.1.7), Beta (B1.351), Gamma (P.1) and Delta (B.1.617.2) could be more infective in human cells compared with SARS-CoV-2 isolated in Wuhan-2019 and the Gamma and Delta variants could be the most infective among them.